Matrix Anisotropy Promotes a Transition of Collective to Disseminated Cell Migration via a Collective Vortex Motion - Su, Chia‐Yi; Matsubara, Tatsuya; Wu, Alex; Ahn, Eun Hyun; Kim, Deok‐Ho (Advanced biology, 2023)
Cells detached and disseminated away from collectively migrating cells are frequently found during tumor invasion at the invasion front, where extracellular matrix (ECM) fibers are parallel to the cell migration direction. However, it remains unclear how anisotropic topography promotes the transition of collective to disseminated cell migration. This study applies a collective cell migration model with and without 800 nm wide aligned nanogrooves parallel, perpendicular, or diagonal to the cell migration direction. After 120 hour migration, MCF7‐GFP‐H2B‐mCherry breast cancer cells display more disseminated cells at the migration front on parallel topography than on other topographies. Notably, a fluid‐like collective motion with high vorticity is enhanced at the migration front on parallel topography. Furthermore, high vorticity but not velocity is correlated with disseminated cell numbers on parallel topography. Enhanced collective vortex motion colocalizes with cell monolayer defects where cells extend protrusions into the free space, suggesting that topography‐driven cell crawling for defect closure promotes the collective vortex motion. In addition, elongated cell morphology and frequent protrusions induced by topography may further contribute to the collective vortex motion. Overall, a high‐vorticity collective motion at the migration front promoted by parallel topography suggests a cause of the transition of collective to disseminated cell migration.